Plasticized polylactic acid nanocomposite films with cellulose and chitin nanocrystals prepared using extrusion and compression molding with two cooling rates: Effects on mechanical, thermal and optical properties. (April 2016) - Herrera, Natalia; Salaberria, Asier M.; Mathew, Aji P.; Oksman, Kristiina
Abstract: Triacetate citrate plasticized poly lactic acid and its nanocomposites based on cellulose nanocrystals (CNC) and chitin nanocrystals (ChNC) were prepared using a twin-screw extruder. The materials were compression molded to films using two different cooling rates. The cooling rates and the addition of nanocrystals (1 wt%) had an impact on the crystallinity as well as the optical, thermal and mechanical properties of the films. The fast cooling resulted in more amorphous materials, increased transparency and elongation to break, (approx. 300%) when compared with slow cooling. Chitin nanocomposites were more transparent than cellulose nanocomposites; however, microscopy study showed presence of agglomerations in both materials. The mechanical properties of the plasticized PLA were improved with the addition of a small amount of nanocrystals resulting in PLA nanocomposites, which will be further evaluated for film blowing and thus packaging applications.